2013
DOI: 10.1038/cmi.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

The liver works as a school to educate regulatory immune cells

Abstract: Because of its unique blood supply, the liver maintains a special local immune tolerogenic microenvironment. Moreover, the liver can impart this immune tolerogenic effect on other organs, thus inducing systemic immune tolerance. The network of hepatic regulatory cells is an important mechanism underlying liver tolerance. Many types of liver-resident antigen-presenting cells (APCs) have immune regulatory function, and more importantly, they can also induce the differentiation of circulating immune cells into re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 143 publications
2
55
0
Order By: Relevance
“…Although this effect prevents the development of sepsis or systemic inflammation, this effect also is the main contributor to immunosuppression and mortality [54]. Endotoxin tolerance has been observed in patients with sepsis, acute liver failure, and cirrhosis [55].…”
Section: Liver Immune Response In Sepsismentioning
confidence: 99%
“…Although this effect prevents the development of sepsis or systemic inflammation, this effect also is the main contributor to immunosuppression and mortality [54]. Endotoxin tolerance has been observed in patients with sepsis, acute liver failure, and cirrhosis [55].…”
Section: Liver Immune Response In Sepsismentioning
confidence: 99%
“…Daclizumab therapy was associated with a significant expansion of regulatory CD56 bright NK cells in vivo and a gradual decline in circulating CD4 + and CD8 + T cells, providing supporting evidence for the existence of an immunoregulatory pathway through which activated CD56 bright NK cells inhibit T‐cell survival . Defined by the differential expression of a combination of CD27 and CD11b, analysis of NK cell subsets indicated that the immature subset was dominant in the liver and that the immature CD27 + CD11b − hepatic NK cell subset was protective against liver metastasis, indicating that the liver maintains a special local immune tolerogenic microenvironment and educates NK tolerant cells …”
Section: Regulatory Nk Cells In Organsmentioning
confidence: 99%
“…12 More importantly, the percentage of NK cells in the liver is known to be nearly five times greater than the percentages in blood or spleen. 13,14 These liver-residing NK cells exert unique phenotypic and functional characteristics, such as immunological memory, suggesting the critical role of NK cells in the liver. 15,16 However, the percentage and absolute number of liver NK cells decrease significantly during the development and progression of HCC.…”
Section: Introductionmentioning
confidence: 99%